2007
DOI: 10.1063/1.2799744
|View full text |Cite
|
Sign up to set email alerts
|

High aspect ratio surface relief structures by photoembossing

Abstract: Photoembossing is a convenient and economical process to form complex surface relief structures in polymer thin films. We have improved the aspect ratio of photoembossed microstructures by adding t-butyl hydroquinone (TBHQ) to the polymerization mixture. The mechanism that is proposed is based on the radical transfer principle, where TBHQ converts acrylate radicals into stable phenol radicals that at elevated temperatures act as latent initiators, thereby controlling the kinetics without changing the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…In the second set of experiments, smooth corrugated polymer surfaces were created by means of a four-step process called photo-embossing [15]. First a so-called photo-polymer layer was spin-coated on glass forming layers approximately 20 µm thick.…”
Section: Methodsmentioning
confidence: 99%
“…In the second set of experiments, smooth corrugated polymer surfaces were created by means of a four-step process called photo-embossing [15]. First a so-called photo-polymer layer was spin-coated on glass forming layers approximately 20 µm thick.…”
Section: Methodsmentioning
confidence: 99%
“…However, the majority of these methods involve photoablation, 21-26 photopolymerization [27][28][29] or photocrosslinking. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Hence, reversible SRG formation has not been reported in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Recently, it has been reported that colorless large SR structures due to mass transfer can be fabricated using materials that do not contain azobenzene compounds. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] It is considered that SR formation is concerned with photoreactioninduced internal diffusion processes. Recently, we have reported that the SR structure is fabricated by spatially patterned ultra-violet (UV) light, even in a general-purpose polystyrene (PS) film.…”
Section: Introductionmentioning
confidence: 99%